(untitled) (Fiep Bulletin - online, 2011)
(INTRODUCTION) Aging is a physiological phenomenon and regressive observable in all living beings, which is characterized by loss of physical and psychological capacities over the years due to the influence of variables such as lifestyle, genetics, accumulated damage and psychological changes. This process still remains as one of the most complex to science, despite the efforts being made, especially since the second half of the twentieth century (FREITAS, 2002). Physical inactivity is a risk factor for chronic diseases later more prevalent in the population (VUORI, 2001). For all that, it becomes increasingly important to determine the activity level of the population, since inactivity causes so many problems, through questionnaires, which are precision instruments, easy to apply and inexpensive. (OBJECTIVE) To analyze the level of physical activity in older of Mossoró-RN city. (METHODOLOGY) The research is descriptive, characterized as a field study. The sample was comprised 75 elderly, 30 male and 35 female, aged between 60 and 87 years, of three quarters of the city. The questionnaire used to determine the level of physical activity was the version eight of the International Physical Activity Questionnaire (IPAQ). (RESULTS) The results showed that, 9.3% are considered very active, 29.3% are actives, 17.3% are irregularly active A, 13.3% are Irregularly Active B and 30.8% are sedentaries. (CONCLUSION) It can be concluded that there is a higher percentage of sedentary elderly among evaluated, but a large part of them still practice some physical activity, whether at home, at work or for leisure.